1973
DOI: 10.1111/j.1532-5415.1973.tb00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Physiological Effects of Stimulation of the Paleocerebellum in Humans

Abstract: Chronically implanted electrodes allowed the repeated stimulation, with different rates and intensities and for variable durations, of the paleocerebellum in 4 patients with intractable muscular hypertonia and also in a patient with epilepsy resistant to antiepileptic drugs. Chronic stimulation of the anterior cerebellum at high rates (100–200 cycles per second) inhibited muscular hypertonus. Chronic stimulation at 10 cycles per second in the patient with epilepsy inhibited the seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
1

Year Published

1974
1974
1982
1982

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 7 publications
0
29
1
Order By: Relevance
“…Chronic electrical stimulation of the anterior cerebellum has been reported to reduce rigidity in patients with motor system disorders (Cooper et al, 1973). The theoretical justification for this procedure stems partially from the observation that decerebrate rigidity in animals decreases with repeated surface electrical stimulation of the paleocerebellum (Sherrington, 1898;Dow and Moruzzi, 1958).…”
mentioning
confidence: 99%
“…Chronic electrical stimulation of the anterior cerebellum has been reported to reduce rigidity in patients with motor system disorders (Cooper et al, 1973). The theoretical justification for this procedure stems partially from the observation that decerebrate rigidity in animals decreases with repeated surface electrical stimulation of the paleocerebellum (Sherrington, 1898;Dow and Moruzzi, 1958).…”
mentioning
confidence: 99%
“…[1][2][3] and Davis et al [4][5][6] independently reported satisfactory results during the past several years in a large group of patients. Sukoff and Ragatz [ 10] reported relief of posthypoxic decere brate rigidity in 2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable success has also been reported in reducing rigidity in pa tients with cerebral palsy following chronic electrical stimulation of the cerebellum [1,3,6,16]. Clinical relief was achieved with high frequency stimulation (200 Hz) [1,3] as well as low frequencies (20 Hz) [16].…”
mentioning
confidence: 87%
“…Electrical stimulation of the surface of the cerebellum has been used to treat a number of neurological disorders since Cooper et al [1] first re ported the clinical and physiological effects of stimulation of the paleocerebellum in man in 1973.…”
mentioning
confidence: 99%